Взаємодія компонентів у системі Ag(2-х)SbхP2хSe(1+5х) (0˂х˂1) - Cабов Віктор; Victor Sabov; Поторій Марія; Potorij Mariia; П'ясецкі Міхал; Michal Piasecki; Філеп Михайло; Filep Mykhailo; Filep Mihály; Погодін Артем; Pogodin Artem; Сабов Мар’ян; et al. (ДВНЗ Ужгородський національний університет, 2021)
Резюме. У почетверній системі Ag–Sb–P–Se формується ряд термічно стабільних фаз з цікавими та перспективними в практичному аспекті властивостями. Серед них, представники сімейства гексатіо-(селено)дифосфатівтернарні Ag4P2Se6 і Sb4(P2Se3)3 та тетрарна AgSbP2Se6, які характеризуються цілим спектром перспективних властивостей: нелінійно оптичними, сцинтиляційними, фотокаталітичними, тощо [1-3]. Сполука AgSbSe2, що належить до напівпровідників типу AIB VX VI 2 (AI – лужний метал, Ag, Cu, Tl; B V – As, Sb, Bi; CVI – халькоген) є перспективним термоелектричним матеріалом [4-6]. Для сполук Ag2Se та Ag7PSe6, окрім високої іонної провідності, притаманна значна термоелектрична ефективність [7, 8]. Можливість поєднання різноманітних фізичних характеристик в одній речовині спонукає до вивчення фазових рівноваг за участю названих матеріалів, зокрема у системі Ag(2-х)SbхP2хSe(1+5х) (0˂х˂1), на основі бінарної сполуки Ag2Se та тетрарної AgSbP2Se6, що становило мету даного дослідження.

Abstract. The system Ag(2-х)SbхP2хSe(1+5х) (0˂х˂1), based on Ag2Se and AgSbP2Se6 is realized in the quaternary system Ag – Sb – P – Se. Pre-synthesized Ag2Se and AgSbP2Se6 were the starting components for the synthesis of samples in the system. The initial components were synthesized from elementary components of high purity taken in stoichiometric ratios by the direct single-temperature method in evacuated up to 0.13 Pa quartz ampoules. The synthesis temperature was 40-50 K higher than the melting points of the components, including intermediates. The compounds were identified by differential thermal (DTA) and X-ray powder diffraction (XRD) analyzes. Two endothermic effects were observed on the thermogram of the Ag2Se compound: at 402 ± 5 K, which corresponds to the polymorphic transformation of Ag2Se, and at 1165 K, which corresponds to the melting of Ag2Se. One endothermic effect was observed on the AgSbP2Se6 thermogram at 740 ± 5 K. The DTA data for both compounds were in good agreement with the literature and confirmed the congruent nature of their melting. According to the X-ray diffraction results, it was established that we obtained a trigonal modification of AgSbP2Se6 and a low-temperature modification of Ag2Se. The obtained powder patterns were completely consistent with the powder patterns calculated according to the literature data. The synthesis of nine samples (x = from 0.05, 0.1, 0.2, 0.4, 0.5, 0.6, 0.8, 0.9, 0.95) was carried out by a method similar to the synthesis of the starting compounds from previously synthesized Ag2Se and AgSbP2Se6. The maximum synthesis temperature was 1250 K, and exposure at this temperature was 72 hours. To the annealing temperature (573 K) cooling was carried out at a rate of 70 K/h. The duration of annealing was 240 hours. The obtained samples were investigated by DTA and XRD methods (DRON 4.07, Cu Kα radiation). Thermograms of samples of the Ag(2-х)SbхP2хSe(1+5х) (0˂х˂1) system was characterized by a significant number of thermal effects, which is evidence of a complex physicochemical interaction in the studied system. The X-ray diffraction results showed that the powder patterns of the samples are characterized by the presence of reflexes that do not belong to the original components. To clarify the nature of the interaction in the system Ag(2-х)SbхP2хSe(1+5х) , samples with x = 0.11 and x = 0.33 were additionally synthesized. By comparing the experimental powder patterns with the calculated for the compounds realized in the quaternary Ag – Sb – P – Se system by literature data and for the corresponding phase mixtures, the phase composition was established and the mechanism of interaction during synthesis with Ag2Se and AgSbP2Se6 in the Ag(2-х)SbхP2хSe(1+5х) (0˂х˂1) system was proposed. According to the obtained data in the system Ag(2-х)SbхP2хSe(1+5х) (0˂х˂1) five phase regions are realized: one two-phase (Ag4P2Se6 and AgSbSe2, at x = 0.33), two three-phase (Ag, Ag7PSe6 and AgSbSe2, at x = 0.11 and Ag4P2Se6, AgSbSe2 and AgSbP2Se6, at 0.33˂x˂1), two four-phase (Ag, Ag2Se, Ag7PSe6 and AgSbSe2, at 0˂x˂0.11 and Ag, Ag7PSe6, Ag4P2Se6 and AgSbSe2, at 0.11˂х˂0.33).
Interaction in the Ag(2-х)SbхP2хSe(1+5х) (0˂х˂1) system
Keywords: РФА; ДТА